Literasi Internet Untuk Meminimalisir Dampak Konten Negatif Pada Ibu-Ibu Pkk Desa Citeras - Helena Nurramdhani Irmanda; Nurul Chamidah (Jurnal Pengabdian UntukMu NegeRI, 2020)
Internet rapid use in daily life has led to lifestyle changes. Internet is not only used by adults but also children. The Family Welfare Empowerment (PKK) action as the vanguard in the family has goals to create a family with noble character. It is important for PKK mothers to understand internet literacy in order to educate their children in healthy internet use so that the negative impact can be minimized. Based on the situation analysis, problems in Citeras village can be formulated, namely the need to increase the understanding of Citeras village PKK mothers regarding internet literacy. The solution to this problem is to conduct training activities on internet literacy and use of parental control applications. This activity aims to improve the competence of PKK mothers so that they can monitor their children in using the internet positively. This training has been carried out well. This is reinforced by the data from the internet usage survey, the high category N-gain value of 96,15, and the results of the survey on the implementation of activities to the community which received a positive response from the participants